Engaging Patients and Caregivers in Research for Pediatric Inflammatory Bowel Disease: Top 10 Research Priorities. Issue 3 (September 2019) - Grant, Amy; Crane, Melissa; Laupacis, Andreas; Griffiths, Anne; Burnett, Dave; Hood, Amanda; Kluthe, Cheryl; Maghera, Muneet; Mann, Malcolm; Mansi, Melissa; Murray, Kate; Trempe, Marie-Josée; et al.
ABSTRACT: Introduction: Including individuals with lived experience in pediatric inflammatory bowel disease (IBD) is essential to establishing a research agenda that is mutually impactful to both those treating and those experiencing the disease. Methods: Using the James Lind Alliance approach to research priority setting, a 10-member steering committee composed of current and former pediatric patients with IBD, caregivers, and clinicians was formed. A national survey, disseminated across Canada, elicited uncertainties which were divided into unanswered and answered research questions. Subsequently a research prioritization survey was disseminated where respondents ranked their top 20 research uncertainties. A final prioritization meeting was held to agree upon the top 10 uncertainties. Results: From 1209 research questions submitted by 363 participants, the list was reduced to 105 indicative questions that were within scope and deemed unanswered in the literature. Via the national research prioritization survey, this list was further reduced. The top 10 uncertainties identified at the final research consensus meeting, with 21 participants from all stakeholder groups, included "What are the causes of IBD?, " "Can IBD be prevented?, " "What role does diet have in the management of pediatric IBD?." Other questions concerned flare ups, biomarkers, optimal patient education, long-term effects of medication and early-diagnosis, role of psychological support, and optimal approach to diagnosis. Conclusion: This research adds a unique perspective by deriving a list of pediatric IBD research uncertainties important by patients and caregivers and clinicians. Abstract : Supplemental Digital Content is available in the text